2017
DOI: 10.1080/13691058.2017.1367420
|View full text |Cite
|
Sign up to set email alerts
|

Long-term health outcomes of childhood sexual abuse and peer sexual contact among an urban sample of behaviourally bisexual Latino men

Abstract: While previous research indicates high rates of childhood sexual abuse among Latino men who have sex with men, few studies have examined the long-term health outcomes of childhood sexual abuse specifically among behaviourally bisexual Latino men. In a sample of 148 behaviourally bisexual Latino men in New York City, we examined associations between childhood sexual abuse and multiple dimensions of adult health: sexual risk behaviours; sexually transmitted infections incidence; polydrug use; depressive symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
6
0
2
Order By: Relevance
“…Some research has focused on racially and/or ethnically homogeneous samples, presumably in order to understand within-group disparities in CSA experiences and long-term consequences. Among Latino MSM, CSA has been linked to depression (Levine et al, 2018;Mattera et al, 2018;Sauceda, Wiebe, & Simoni, 2016), stress (Mattera et al, 2018), heavy drinking or problematic alcohol use (Levine et al, 2018;Wang et al, 2017), and sexual risk behavior Martinez et al, 2016;Mattera et al, 2018). In a cross-sectional study of Latino MSM living with HIV (Sauceda et al, 2016), those with a history of CSA reported more depression and worse HIV medication adherence than men without CSA history.…”
mentioning
confidence: 99%
“…Some research has focused on racially and/or ethnically homogeneous samples, presumably in order to understand within-group disparities in CSA experiences and long-term consequences. Among Latino MSM, CSA has been linked to depression (Levine et al, 2018;Mattera et al, 2018;Sauceda, Wiebe, & Simoni, 2016), stress (Mattera et al, 2018), heavy drinking or problematic alcohol use (Levine et al, 2018;Wang et al, 2017), and sexual risk behavior Martinez et al, 2016;Mattera et al, 2018). In a cross-sectional study of Latino MSM living with HIV (Sauceda et al, 2016), those with a history of CSA reported more depression and worse HIV medication adherence than men without CSA history.…”
mentioning
confidence: 99%
“…Studies that did not utilize previously validated measures were operationalized in the current study as investigator-created. Mattera et al. (2018) , asked Latino bisexual men closed-ended questions based on definitions of statutory rape to define childhood sexual assault.…”
Section: Resultsmentioning
confidence: 99%
“…CEA and CSA were not significantly associated with prescription drug misuse or illicit drug use. Mattera et al. (2018) Study design: Cross-sectional Sample Size: 148 Population: Bisexual Latino men Measure name: Investigator created- CSA type Operationalization: Individual ACE ACE prevalence: 1+ CSA = 22% Outcome: Polydrug use Measure: Investigator created Analysis: Logistic Regression CSA was not significantly associated with past four-month polydrug use.…”
Section: Methodsmentioning
confidence: 99%
“…La mayoría de los artículos se enfocaron en los im pactos de la VSI (n = 22) en varias dimensiones: salud mental, salud sexual, co m portamientos de riesgo y violencia. Varios estudios encontraron asociaciones entre la VSI con distrés mental, estrés postraumático y estrés crónico (17-18, 21, 24, 29); sínto mas psiq uiátricos en la adolescencia (23); sínto mas depresivos, depresión mayor e ideación suicida (21,24,29,40); y alteraciones en el desarrollo de la identidad en varios do minios (psicológico, relacional, de género, aspiracional y espiritual) (41).…”
Section: Efec Tos De La Vsi En Varonesunclassified
“…Estos incluyen la ocurrencia de VIH (20,(31)(32), la adherencia a antirretrovirales (36) y efectos sindémicos negativos (incluyendo coocurrencia de riesgo de VIH , uso de sustancias y violencia de pareja) (31). Varios estudios deter minaron asociaciones con co m portamientos de riesgo co m o el uso de sustancias psicoactivas (19,21,31), consum o excesivo de alcohol (27,31), mayor número de parejas sexuales (31), y trabajo sexual y otras conductas sexuales de riesgo (29,31,36).…”
Section: Efec Tos De La Vsi En Varonesunclassified